Implementasi Literasi Digital Di Kalangan Mahasiswa Pendidikan Biologi ITS NU Pasuruan - Nanda D.A, Ema; Maisaroh, Siti; Fitriyah, Siti; Diniyah, Chikmah (Jurnal Likhitaprajna, 2023)
This study aims to determine the effectiveness of digital literacy implementation among students. The research method used is a survey method by distributing questionnaires online through the google form platform. Based on the results of research conducted on 31 female students of the ITS NU Pasuruan biology education study program class 22d-A, it was found that 74.2% or 23 of the 31 respondents used gadgets every day, while 19.4% or 6 of the 31 respondents used gadgets every day but rarely used gadgets. And the remaining 6.5% or 2 out of 31 only use gadgets several times a week. So it can be concluded that almost all biology education students in class 22d-A stated that they use gadgets every day, with a percentage of 74.2% or 23 out of 31 respondents. All 22d-A ITSNU Pasuruan biology education study program students have access and understanding of sophisticated technology, but not all of them have an interest or preference for digital literacy. The current learning process also utilizes technology according to current needs. It is imperative that individuals are able to improve their digital literacy skills. This is because digital technology is also very supportive of a person's process in developing themselves and seeking as much knowledge as possible without any time and space limitations.